A randomized comparative study of the effects of oral and topical estrogen therapy on the lower urinary tract of hysterectomized postmenopausal women - Long, Cheng-Yu; Liu, Cheng-Min; Hsu, Shih-Cheng; Chen, Yung-Hung; Wu, Chin-Hu; Tsai, Eing-Mei (Fertility and sterility, 2006)
To compare the effects of oral and vaginal estrogen therapy (ET) on the lower urinary tract in postmenopausal women with prior hysterectomy. Randomized, prospective study. Tertiary teaching hospital. Fifty-seven hysterectomized, postmenopausal women. Patients were randomized to receive either oral (0.625 mg of conjugated equine E per tablet; n = 27) or topical (0.625 mg conjugated equine E per 1 g vaginal cream; n = 30) E, administered once daily. All subjects had E 2 measurements, urinalysis, pelvic examination, introital color Doppler ultrasonographies, and personal interviews with the Bristol Female Lower Urinary Tract Symptoms Questionnaires before and 3 months after ET. A higher serum level of E 2 was noted in the oral group compared with the topical group after ET. The post-ET pulsatility index of periurethral vessels and bladder neck revealed statistically significant decreases in both groups. The incidences of urinary frequency and nocturia were significantly decreased after 3 months of ET in both groups. Changes in the incidence of other symptoms, including stress incontinence and urge incontinence, were not statistically significant. However, subjective improvement of stress incontinence was found in 72.7% of the oral group and 60% of the topical group. The results suggest that ET alone, by an oral or vaginal route, could increase the blood flow around the bladder neck and mid-urethra and relieve the symptoms of overactive bladder and stress incontinence in postmenopausal women with prior hysterectomy. In addition, vaginal preparations are as effective as systemic therapy at the lower serum level of E 2.